Present distribution of Heterotheca latifolia Buck. in San Luis (Argentine Republic) (Semiárida, 2020)
This research was carried out in order to document the occurrence of Heterotheca latifolia Buck. and map its distribution. It was performed by searching along national and provincial roads, being the collecting stations placed every 25 km, on both sides of them, and in both tilled and untilled fields. At present, this weed has covered nearly the whole Province, including natural grasslands and agriculture lands, not having be a detected on the central hilly region and the North Western one.
Keywords: weed; adventitious; distribution; Heterotheca latifolia